Assessment of 222Radon Concentration and Annual Effective Dose in Drinking Water in Bardarash, Kurdistan Region of Iraq - Kareem, Idrees Majeed; Ahmed , Ahmed Mohamed (Engineering, Technology & Applied Science Research, 2023)
The study aims to determine the concentration of radon to assess the radioactive risk in groundwater in Bardarash, Kurdistan region, Iraq, which relies on groundwater as its primary source of water. Fifty samples were collected from wells for water use and were evaluated with RAD7-active Durridge Electronic Detector. Radon concentrations ranged from 0.93±0.43 Bq/l to 11.39±1.86 Bq/l, with a mean of 7.22 Bq/l and a standard deviation of 2.5. The results were used to estimate the annual effective doses of three categories. The annual effective doses of ingestion of groundwater ranged from 14.26 to 174.61 μSv/y with an average value of 110.73 μSv/y, 19.02 to 232.81 μSv/y with an average value of 147.67 μSv/y, and 4.41 to 54.05 μSv/y with an average value of 34.27 μSv/y, for infants, children, and adults, respectively. Furthermore, the annual effective dosage obtained in inhalation ranged from 2.34 to 28.70 μSv/y, with an average of 18.20 μSv/y. The total annual effective dose ranged from 16.60 to 203.31 μSv/y with an average value of 128.93 μSv/y, 21.35 to 261.51 μSv/y with an average value of 165.84 μSv/y, and 6.76 to 82.75 μSv/y with an average value of 52.48 μSv/y for infants, children, and adults, respectively. The majority of the samples had radon concentrations and effective dosages that were less than the maximum permissible limit of 11.1 Bq/l. This indicates that the majority of the samples are drinkable and safe to consume.